Lectotypifications of some Indian Ceropegia (Apocynaceae: Ceropegieae) - Singh, Rajeev Kumar (Phytotaxa, 2015)
Eight binomials of six recognized species of Ceropegia are lectotypified: C. albiflora Hooker f., C. fantastica Sedgwick, C. lanceolata Wight, C. mysorensis Wight, C. pubescens Wallich, C. pusilla Wight & Arnott, C. sphenanantha Wight, and C. walkerae Wight.